Natural products extract effect on bone integration around orthodontic micro-implant: An experimental study - Hamed Al-Sultan, Mustafa Muath; Al-Khatib, Ali Rajih (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Bone integration around orthodontic implant is a matter of concern for their stability. This study was conducted to estimate calcium and phosphorous level in after insertion of orthodontic implant. Methods: Twenty five white mature male rabbits, classified into 5 groups: one control and four experimental, with five rabbits for each group were used. Fifty orthodontic implants were used, 2 micro-implant for each tibia. Four different natural products extract were used in this study that included Curcumin 15mg/kg, Nigella Sativa oil 0.25 ml/kg, Cissus Quadrangularis 500mg/kg and Virgin Coconut oil 1 ml/kg. Each product was given to certain experimental group started from the day of implant insertion for four weeks healing period. The biochemistry evaluation was conducted involving calcium and phosphorus level in serum. Results: Significant difference in serum calcium levels were detected between Curcumin, Nigella Sativa oil from side and control group on the other side. Conclusion: Systemic Curcumin and Nigella sativa oil may be used for possibly enhancing bone response around orthodontic implant as reflected by lower serum calcium level as compared to control group.